Acute caffeine supplementation and live match-play performance in team-sports: A systematic review (2000-2021) - Arguedas-Soley, A.; Townsend, I.; Hengist, A.; Betts, J. (Journal of Sports Sciences, 2022)
Caffeine is a psycho-active stimulant that can improve physical and cognitive performance. We systematically reviewed the evidence on the effects of acute caffeine ingestion on physiological parameters, physical and technical-skill performance during high-performance team-sport match-play. Following PRISMA guidelines, studies were identified using scientific databases (PubMed, Web-of-Science, Scopus, and SPORTDiscus) in February 2021. Of 281 results, 13 studies met inclusion, totalling 213 participants. Included studies adopted the randomised double-blinded cross-over design, involving caffeine and control conditions. In studies reporting physiological variables, responses to caffeine included higher peak (n=6/ 8 [n/ total studies measuring the variable]) and mean (n=7/ 9) heart rates, increased blood glucose (n=2/ 2) and lactate (n=2/ 2) concentrations. Improvements in physical performance were widely documented with caffeine, including greater distance coverage (n=7/ 7), high-speed distance coverage (n=5/ 7) and impact frequencies (n=6/ 8). From three studies that assessed technical-skills, it appears caffeine may benefit gross-skill performance, but have no effect, or negatively confound finer technical-skill outcomes. There is compelling evidence that ingesting moderate caffeine doses (~3 to 6 mg·kg-1) ~60 minutes before exercise may improve physical performance in team-sports, whereas evidence is presently too scarce to draw confident conclusions regarding sport-specific skill performance.